1981
DOI: 10.1029/ja086ia12p10049
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for magnetic field reconnection at the Earth's magnetopause

Abstract: Eleven passes of the ISEE satellites through the frontside terrestrial magnetopause (local time 9 -'17 h; GSM latitude 2 0 -43 0 N) have been identified, where the plasma velocity in the magnetopause and boundary laver was substantially larger than in the magnetosheath. This paper examines the nature of°the plasma flow, magnetic field, and energeticparticle fluxes in these regions, with a view to determining whether the velocity enhancements can be explained by magnetic-field reconnection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
467
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 716 publications
(503 citation statements)
references
References 36 publications
27
467
0
2
Order By: Relevance
“…The reconnection bulge travels from the reconnection point around the magnetopause at approximately 400 km á s )1 (e.g. Sonnerup et al, 1981) and so will cover 3.8 R E in one minute. The average inter-FTE timing for events A to E is 5.8 min so a timing di erence of say 3 min may create some confusion concerning the`true' sequence of events.…”
Section: B 4 January 1998mentioning
confidence: 99%
“…The reconnection bulge travels from the reconnection point around the magnetopause at approximately 400 km á s )1 (e.g. Sonnerup et al, 1981) and so will cover 3.8 R E in one minute. The average inter-FTE timing for events A to E is 5.8 min so a timing di erence of say 3 min may create some confusion concerning the`true' sequence of events.…”
Section: B 4 January 1998mentioning
confidence: 99%
“…Many previous studies which addressed the location of the reconnection line have concentrated on the observation of high-speed plasma flows in the boundary layers of the magnetopause and their interpretation in terms of the magnetic reconnection process [Paschmann et al, 1979;Sonnerup et al, 1981;1995;Gosling et al, 1990Gosling et al, , 1991Phan et al 2000]. These methods determine the general direction of the location of the reconnection line relative to the spacecraft but do not address the local condition at the reconnection site.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Magnetic reconnection has been shown to occur somewhere at the Earth's magnetopause for any orientation of the IMF [e.g., Sonnerup et al, 1981;Kessel et al, 1996;Fuselier et al, 1991Fuselier et al, , 2000. More typical than the purely southward or northward IMF are conditions with a significant IMF westeast component (B Y 6 ¼ 0).…”
Section: Introductionmentioning
confidence: 99%
“…[2] The occurrence of reconnection at the subsolar [e.g., Paschmann et al, 1979;Sonnerup et al, 1981] and flank [e.g., Gosling et al, 1986;Phan et al, 2001] magnetopause has been well established by single spacecraft in-situ observations. Remote sensing methods have indicated the presence of an X-line spanning a large portion of the dayside magnetopause during southward IMF [Fuselier et al, 2002;Pinnock et al, 2003], but this has not been confirmed by in-situ measurements.…”
Section: Introductionmentioning
confidence: 99%